Growth dynamics and physiological response of selected forestry species to CO2 enriched atmosphere - Anusha R.M (Academy of Climate Change Education and Research, 2019)
Terminalia arjuna, Terminalia bellirica and Terminalia chebula are important medicinal plants and part of Triphala, there is less study about the adaptation and mitigation of these species to elevated CO2. This study is helpful to understand about the adaptive and mitigative and biochemical efficiency of these plants. Under elevated these three species are showed a better response in elevated CO2 800ppm over ambient 400ppm. The plant height, leaf length and width, stem diameter, number leaves and branches, root length, are higher in elevated 800ppm CO2 over ambient 400ppm as well as the biochemical properties like total chlorophyll and carotenoids, ascorbic acid, protein, proline, total sugar are increased dramatically at 800ppm over 400ppm. The photosynthetic rate was higher in elevated CO2 in all seasons (winter, spring, and summer), stomatal conductance was higher in 800ppm spring and lower at summer. The intercellular CO2 concentration was higher in plants grown in 800ppm T.chebula in winter in the summer season. Transpiration rate was higher in winter and reduced over ambient in summer. Night respiration is less in T.arjuna compared to ambient, and there is a fluctuation concerning seasonality and species. Carbon sequestration, carbon partitioning, carbon mitigation and carbon stocks are high in elevated CO2 growing plants except for T.bellirica. Organic carbon was higher in elevated CO2 than ambient. Potassium, phosphorous and total nitrogen they with species and change in concentration according to elevated CO2. The plants grown in elevated CO2 are healthier than ambient condition and increases the health-promoting characters. These species are more adaptive and show mitigation efficiency and good biochemical efficiency. In future more studies needed to know about the response of plants towards elevated CO2.